Characterization of COVID-19 cases in the formal and informal settlements in Dagoretti sub-county Kenya, 2020 - Florence Wanjiru Mugo; Ahmed Abade Mohamed; Peter Kabetu Njenga; Maurice Owiny; Fredrick Odhiambo (Journal of Interventional Epidemiology and Public Health)
Introduction: COVID-19 posed a serious public health threat to all ages. In Kenya, it was first detected on March 13, 2020, in its capital - Nairobi, which remained the epicenter of the disease thereafter. Dagoretti is one area that has both formal and informal residencies and showed a marked increase of cases; from a total of nine in March to 1219 in July 2020. The upsurge prompted us to describe the cases as they were being identified through contact tracing. Methods: This was a cross-sectional study that involved the review of COVID-19 data from 1st March to 31st July 2020 using a line list. We reviewed data for all COVID-19 cases and their contacts. We generated measures of central tendency for continuous variables and frequencies and proportions for categorical variables. Results: Of the 1,620 COVID-19 records analyzed, 98% (1580) had no contact history with a case. The median age was 42 (IQR: 20.5 – 64.5) years. The majority 59.5% (964/1620) were males with 32.7% (529/1620) from the age group of 31-40 years. The formal settlements had higher infections at 85.7% (1,389/1,620). All 16 deaths (100%) were from formal residencies out of which 62.5% (10/16) had comorbidities. Conclusion: COVID-19 disproportionately affected the formal dwellers in the early days of the pandemic. The highest mortality occurred in cases with comorbidities. We recommended targeted advocacy and scale-up of COVID-19 awareness to diabetic and hypertensive cases in both residencies.